Evaluation of the accuracy, ease of use and limit of detection of novel, rapid, antigen-detecting point-of-care diagnostics for SARS-CoV-2 - Krüger, Lisa; Gaeddert, Mary; Köppel, Lisa; Brümmer, Lukas E.; Gottschalk, Claudius; Barreto Miranda, Isabel; Schnitzler, Paul; Kräusslich, Hans-Georg; Lindner, Andreas; Nikolai, Olga; Mockenhaupt, Frank Peter; Seybold, Joachim; et al. (medRxiv, 2020)
Abstract Background Reliable point-of-care (POC) diagnostics not requiring laboratory infrastructure could be a game changer in the COVID-19 pandemic, particularly in the Global South. We assessed performance, limit of detection and ease-of-use of three antigen-detecting, rapid POC tests (Ag-RDT) for SARS-CoV-2. Methods This prospective, multi-centre diagnostic accuracy study recruited participants suspected to have SARS-CoV-2 in Germany and the UK. Paired nasopharyngeal swabs (NP) or NP and/or oropharyngeal swabs (OP) were collected from participants (one for clinical RT-PCR and one for Ag-RDT). Performance of each of three Ag-RDTs was compared to RT-PCR overall, and according to predefined subcategories e.g. cycle threshold (CT)-value, days from symptoms onset, etc. In addition, limited verification of the analytical limit-of-detection (LOD) was determined. To understand the usability a System Usability Scale (SUS) questionnaire and ease-of-use (EoU) assessment were performed. Results Between April 17th and August 25th, 2020, 2417 participants were enrolled, with 70 (3.0%) testing positive by RT-PCR. The best-performing test (SD Biosensor, Inc. STANDARD Q) was 76×6% (95% Confidence Interval (CI) 62×8-86×4) sensitive and 99×3% (CI 98×6-99×6) specific. A sub-analysis showed all samples with RT-PCR CT-values <25 were detectable by STANDARD Q. The test was considered easy-to-use (SUS 86/100) and suitable for POC. Bioeasy and Coris showed specificity of 93×1% (CI 91×0%-94×8%) and 95×8% (CI 93×4%-97×4%), respectively, not meeting the predefined target of ≥98%. Conclusion There is large variability in performance of Ag-RDT with SD Biosensor showing promise. Given the usability at POC, this test is likely to have impact despite imperfect sensitivity; however further research and modelling are needed.